The effectiveness of physics subject-specific pedagogy based on indigenous knowledge to improve students’ patriotism - Purwita, Tanty Dwi; Rosana, Dadan (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2020)
Indigenous knowledge can develop ways of thinking, creativity, and dynamics of indigenous peoples in an area. This study aimed to know the effectiveness of Physics Subject-specific Pedagogy (SSP) based on indigenous knowledge to improve students' patriotic character. This study focused on SSP product implementation through an experimental method, i.e., one group pretest-posttest design. The Physics SSP adopted the 4D research by Thiagarajan. This product consisted of a syllabus, lesson plans, worksheets, questionnaires, and observation sheets. This research was conducted at Senior High School 1 Turen, Malang, with two different treatments on sixty-six eleventh-grade students in the academic year of 2019/2020. The analyses performed were descriptive and analytical test analysis. Based on the homogeneity and normality test results, all pretest and posttest scores in both classes had homogeneous data. However, the data were not normally distributed. Based on the regression coefficient and the effect size value, the Physics SSP, based on indigenous knowledge, obtained an effect size value of 14.12%. However, the obtained value indicated that the effect of Physics SSP was in a low category.